A produção de conhecimento em Psicologia: a análise do comportamento - TOURINHO, Emmanuel Zagury (2016)
This paper discusses radical behaviorist approach to Psychology as a science of behavior, highlighting three sets of issues: a) the notion of knowledge adopted, particularly in its rejection of logical positivist principles, and its accordance to an instrumental and relational view; b) an interpretation of Psychology as a field of knowledge in which philosophical, scientific and applied contents are articulated; and c) a research program of psychological phenomena based on an externalist view of the subject matter and a selectionist conception of causality. The analysis contrasts radical behaviorism to modern conceptions of men, emphasizing its scope and its critical and innovatory character in Psychology and in culture in general.